The body in motion. An introduction - Breitenmoser, Kurt.; Burt, Vanessa; Dunn, Andrew; Video Education Australasia (Bendigo, Vic. : VEA, 2010)
'The human body is always on the move. Whether we are jumping, running or sitting still; blood is pumping, muscles are contracting, and joints are moving. The body's internal systems perform complex processes every second of every day, so we can spend our time doing whatever we need to. This Australian-made, curriculum fit program takes us inside the human body, showing us just how the musculoskeletal and cardio-respiratory systems work and how they influence and respond to movement. This information-packed program is presented in a clear and logical format, with vivid animations and real-life examples that will engage viewers from start to finish'--Container.
Introduction -- The skeletal system -- The muscular system -- The respiratory system -- The circulatory system -- Conclusion.
Program support notes available on publisher's website.
Producer/director, Kurt Breitenmoser ; writer, Vanessa Burt.
Narrator: Andrew Dunn.
DVD.
Keywords: Human physiology; Musculoskeletal system; Respiratory organs; Cardiovascular system